One-Pot Synthesis of Boron-Doped Polycyclic Aromatic Hydrocarbons via 1,4-Boron Migration - Zhang, Jin-Jiang; Tang, Man-Chung; Fu, Yubin; Low, Kam-Hung; Ma, Ji; Yang, Lin; Weigand, Jan J.; Liu, Junzhi; Yam, Vivian Wing-Wah; Feng, Xinliang (Angewandte Chemie International Edition, 2021)
Herein, we demonstrate a novel one-pot synthetic method towards a series of boron-doped polycyclic aromatic hydrocarbons (B-PAHs, 1 a–1 o), including hitherto unknown B-doped zethrene derivatives, from ortho-aryl substituted diarylalkynes with high atom efficiency and broad substrate scopes. A reaction mechanism is proposed based on the experimental investigation together with the theoretical calculations, which involves a unique 1,4-boron migration process. The resultant benchtop-stable B-PAHs are thoroughly investigated by X-ray crystallography, cyclic voltammetry, UV/Vis absorption, and fluorescence spectroscopies. The blue and green organic light-emitting diode (OLED) devices based on 1 f and 1 k are further fabricated, demonstrating the promising application potential of B-PAHs in organic optoelectronics.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 1; 4-boron migration; boron doping; nanographenes; organic electronics; polycyclic aromatic hydrocarbons (PAHs)